Analisis CSR Terhadap Kinerja Perusahaan - Kholis, Nur (STIE Surakarta, 2015)
Purpose of this study was to obtain empirical evidence that Corporate Social Responsibility ( CSR ) has an influence on the corporate performance in showed with ROA (Return on Assets ) and ROE (Return on Equity ). This study used secondary data obtained from the companys annual report, published in the Stock Exchange s website and the official website of the company. Techniques used in sampling in this research is using purposive sampling method . Based on the results of the study founding that the variables of Corporate Social Responsibility ( CSR ) significant difference between Corporate Social Responsibility ( CSR ) on the financial performance in showed with Return on Assets ( ROA ), Return on Equity ( ROE ) .